PRELIMINARY PHYTOCHEMICAL SCREENING AND ANTI-INFLAMMATORY EFFECT OF THE AQUEOUS EXTRACT OF TABERNAEMONTANA DIVARICATA FLOWER IN WISTER RATS - Garga, Deepankar; Das, Trishna (International Journal of Current Pharmaceutical Research, 2017)
Objective: To determine the phytochemical analysis and anti-inflammatory effect of the aqueous extract of Tabernaemontanadivaricata flower in Wister Rats. Methods: The aqueous extract of fresh flowers of the plant Tabernaemontanadivaricata (family-Apocyanaceae) were prepared and analyzed for phytochemical constituents using standard methods. The anti-inflammatory activity of the plant extracts was examined with the help of rat models by taking diclofenac as a standard drug against T. divericata oil extract by using carrageenan induced rat paw edema method with the help of the instrument plethesmometer. Results: The present experiment shows the phytochemical analysis, anti-inflammatory activity of the aqueous extract of fresh flowers of the plant Tabernaemontanadivaricata (family-Apocyanaceae). Various phytochemical analysis revealed the presence of saponins, flavonoids, glycosides, steroids, proteins, phenols, amino acids and tannins. The oil extract of the plant showed much effective anti-inflammatory activity against the standard drug. Conclusion: It can be concluded aqueous extract of the flower of the plant Tabernaemontanadivaricata (family-Apocyanaceae) contain the high presence of phytochemicals. This extract was found to possess promising antimicrobial activity when compared with the standards.